1997
DOI: 10.1128/iai.65.5.1786-1792.1997
|View full text |Cite
|
Sign up to set email alerts
|

The spv genes on the Salmonella dublin virulence plasmid are required for severe enteritis and systemic infection in the natural host

Abstract: The pathogenic role of the spv (Salmonella plasmid virulence) genes of Salmonella dublin was determined in the natural, bovine host. Since the lack of overt signs of enteritis or enterocolitis due to Salmonella infections in mice has limited the development of a convenient experimental system to study enteric disease, we used calves to study the contribution of the spv genes to S. dublin-induced salmonellosis. Since the SpvR transcriptional regulator is required for expression of the spvABCD operon, we constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 49 publications
0
63
0
3
Order By: Relevance
“…The next morning, a volume with the expected concentration of Salmonella Typhimurium was mixed with 1 L of milk replacer and 2.5 g of sodium bicarbonate, 2.5 g of magnesium trisilicate, and 2.5 g magnesium hydroxide to alkalinize the abomasum. 10 Slight differences in inoculum dose occurred based on variability in the overnight growth of the isolate. The inoculum in milk was fed to the calf at the morning feeding on day 0.…”
Section: Challenge Modelmentioning
confidence: 99%
“…The next morning, a volume with the expected concentration of Salmonella Typhimurium was mixed with 1 L of milk replacer and 2.5 g of sodium bicarbonate, 2.5 g of magnesium trisilicate, and 2.5 g magnesium hydroxide to alkalinize the abomasum. 10 Slight differences in inoculum dose occurred based on variability in the overnight growth of the isolate. The inoculum in milk was fed to the calf at the morning feeding on day 0.…”
Section: Challenge Modelmentioning
confidence: 99%
“…To demonstrate that the macrophage phenotype de®ned for the spv locus in S. typhimurium is not speci®c to that serovar, we tested wild-type S. dublin SL2260 and the corresponding spvR mutant SL2403 (Libby et al, 1997) in the human macrophage assay. The results of a time course experiment, shown in Fig.…”
Section: Detached Macrophages Contain Proliferating Bacteriamentioning
confidence: 99%
“…The ®ve Salmonella spvRABCD genes were originally discovered on large plasmids present in certain serovars belonging to the S. enterica subspecies I lineage Guiney et al, 1994;. The plasmid-encoded spv locus was shown to be required for progressive systemic infection by strains pathogenic for mice and for the virulence of host-adapted serovars in their corresponding animal hosts (Chikami et al, 1985;Gulig and Curtiss, 1987;Barrow et al, 1987;Heffernan et al, 1987;Danbara et al, 1992;Wallis et al, 1995;Libby et al, 1997). Recently, the spv genes have been found to have a wide distribution among ancestral lineages of S. enterica, being present on the chromosome in subspecies II, IIIa and VII, as well as in some isolates of subspecies IV (Boyd and Hartl, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence obtained in vivo suggests that the spv genes act to enhance bacterial replication in macrophages (Fields et al, 1986;Gulig and Doyle, 1993). Recently, studies of Salmonella infection in bovine monocyte-derived macrophages have indicated that the spv genes are required for bacterial growth (Libby et al, 1997). Furthermore, expression of the spv genes is required for Salmonella strains to induce cytotoxicity in infected human monocyte-derived macrophages, characterized by cell detachment and eventual apoptosis (Libby et al, 2000).…”
Section: Introductionmentioning
confidence: 99%